This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Lecture 8 Example: Recall that if F : U Y and G : U Z are differentiable at a U , then so is H = ( F,G ) : U Y Z and, further, H a ( h ) = ( F a ( h ) ,G a ( h )) . Conversely, if H is differentiable at a then so are F and G . [Let P : Y Z Y be firstfactor projection: P ( y,z ) = y . This is lin ear and bounded (if Y Z has the norm given by, say, k ( y,z ) k = k y k k z k then k P ( y,z ) k k ( y,z ) k ); Thus, P L ( Y Z,Y ) and so P is differentiable, with P ( b,c ) = P for b Y,c Z . Now F = P H is differentiable at a by the chain rule and F a ( h ) = P ( F ( a ) ,G ( a )) H a ( h ) = P ( H a ( h )) A similar argument applies to G .] Consequence: a map F : R m R n is differentiable at a R m iff its components are all differentiable at a . F ( a ) = ( f 1 ( a ) ,...,f n ( a )) . Interlude: Operator norm on M n R . Let X be a Hilbert space. The adjoint of A L ( X ) is A * L ( X ) given by x,y X ( y  A * x...
View Full
Document
 Summer '10
 Staff
 Algebra

Click to edit the document details